2022
DOI: 10.1021/acsnano.1c06777
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidase-like Active Nanomedicine with Dual Glutathione Depletion Property to Restore Oxaliplatin Chemosensitivity and Promote Programmed Cell Death

Abstract: The nanocatalytic activity of nanozymes provides a vision for tumor treatment. However, the glutathione (GSH)-related antioxidant defense system (ADS) formed on the basis of excessive GSH in the tumor microenvironment limits its catalytic activity. Here, dendritic mesoporous silica nanoparticles (DMSNs) were employed as nanocarrier; ultrasmall Fe3O4 nanoparticles, Mn2+ ions, and glutaminase inhibitor Telaglenastat (CB-839) were subsequently integrated into large mesopores of DMSNs, forming DMSN/Fe3O4–Mn@CB-839… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(87 citation statements)
references
References 64 publications
2
85
0
Order By: Relevance
“…Mesoporous silica nanoparticles are another important platform as inorganic drug delivery carriers for tumor treatment. They have the advantages of low side effects, good biocompatibility and stability, relatively uniform size and a large specific surface area [ 307 , 308 ]. For example, Jang and colleagues developed hybrid mesoporous silica nanoparticles functionalized with β-cyclodextrin and 4-(phenylazo) benzoic acid for improved on-demand drug release.…”
Section: Stimuli-responsive Targeting Strategiesmentioning
confidence: 99%
“…Mesoporous silica nanoparticles are another important platform as inorganic drug delivery carriers for tumor treatment. They have the advantages of low side effects, good biocompatibility and stability, relatively uniform size and a large specific surface area [ 307 , 308 ]. For example, Jang and colleagues developed hybrid mesoporous silica nanoparticles functionalized with β-cyclodextrin and 4-(phenylazo) benzoic acid for improved on-demand drug release.…”
Section: Stimuli-responsive Targeting Strategiesmentioning
confidence: 99%
“…Ferroptosis, a newly defined type of programmed cell death, is closely related to oxidative stress and the disruption of redox homeostasis is also crucial for the chemoresistance of tumour cells ( 159 ). Wu et al ( 160 ) indicated that nanodrugs with silica particles used as carriers are able to dissolve and release Fe 3 O 4 particles and glutaminase inhibitors under acidic conditions, thus consuming glutathione in tumour cells and reversing the drug resistance of tumour cells to oxaliplatin by inducing ROS-dependent ferroptosis. Wang et al ( 161 ) indicated that ovarian tumour domain-containing ubiquitin aldehyde-binding protein 1 (OTUB1) and solute carrier family 7 member 11 (SLC7A11) directly bind to circ_BGN as RNA binding proteins, and circ_BGN significantly enhances OTUB1-mediated SLC7A11 deubiquitination, thereby suppressing ferroptosis.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…CDT that employs the famous Fenton reaction to produce highly deleterious reactive oxygen species (ROS) in cancer cells has been increasingly investigated in the past decade, one of which is the so-called ferroptosis therapy (i.e., FT) based on iron nanoparticles. As a peculiar modality for cancer treatment, ferroptosis is an oxidative stress-induced cell death marked by lethal lipid peroxide (LPO) that is different from apoptosis, necrosis, and autophagy. For example, ultrasmall Fe 3 O 4 and Mn 2+ co-loaded mesoporous silica nanoparticles have been constructed to achieve efficient ferroptosis by a peroxidase-like Fenton reaction . A high-performance self-cascade pyrite nanozyme has been fabricated for synergistic tumor ferroptosis–apoptosis, resulting in a thousand-fold catalytic activity compared to that of conventional Fe 3 O 4 .…”
Section: Introductionmentioning
confidence: 99%